Kajian strategis dan prioritas pembangunan pendidikan menengah untuk meningkatkan mutu pendidikan di Pulau Madura - Priyono Tri Febrianto; Sulaiman Sulaiman (Masyarakat, Kebudayaan dan Politik, 2014)
Efforts in quality improvement and development of education in the era of regional autonomy are not only the responsibility of the central government and provincial governments, but also the responsibility of local governments. Quality improvement and development of education thus become strategic issues for any local government. This study aims to address issues related to: (1) the condition of school facilities and infrastructure (2) the role of school committees which is not optimal; (3) the absence of equitable distribution of teachers; and (4) the lack of Information and Communication Technology/ICT-based learning application in in secondary schools. The research was conducted in four districts, namely Bangkalan, Sampang, Pamekasan and Sumenep. The main theory employed in this study is the School Based Management (SBM) or the so-called School Based Management (SBM). The population was students, parents and teachers. The total number of samples was 250 people comprising 100 students, 100 parents and 50 teachers. The research data were obtained from primary and secondary data. The study yielded a number of key findings. First, 90% of High School (or its equivalent) teachers master the materials taught. This is due to fact that the materials taught are in accordance with the education qualification of the teacher. Secondly, the mismatch found in Madurese high schools was apparently caused by the lack of educators with suitable qualification for the subjects they teach concurrently. Almost all secondary teachers in Madura island require trainings related to the development of competency for mastering the subject materials. The last but not the least, the majority of teachers still apply simple learning methods. Although the method applied by teachers are generally similar, there are significant differences between the favorite schools and the other schools.